Irrigation frequency and doses of polymer hydro retainer in seedlings of coffee formation - Mukeshambala, Franchement Franchement; Guimrães, Rubens José; Tavares, Gilmar; Souza, Antonio Jackson Jesus (Coffee Science - ISSN 1984-3909, 2014)
Without enough water can not install a pond. There hydro retainers polymers capable of absorbing water and releasing it gradually. In order to evaluate the efficiency of using different doses of these polymers on substrates of coffee seedlings at different irrigation frequency, were two experiments, one in the bag and another seedling seedlings in tubes, in Sector Cafeicultura, Departamento de Agricultura, da Universidade de Lavras, Minas Gerais, in a greenhouse covered with polyethylene film and shading 50%, from October 2011 to March 2012. In both experiments were the designs into blocks and split plot scheme for analysis of 6 doses of polymer (in the sub plots) X 5 water levels (in installments) in 4 replicates. The six doses tested were: 0, 5, 10, 15, 20 and 25% of the gel volume in the polymer substrate (1500g dry polymer 400 liters hydrated in water) both in the experiment as sachets in the tubes. The irrigation of the seedlings in tubes were: Level 1: Twice / day; Level 2: Once / day; Level 3, 4, 5: 1, 2, 3 days without water. In the experiment in bags, irrigation levels were: Level 1: all days (1 time / day), Level 2, 3, 4, 5: 1, 2, 3, 4 days without water. It is concluded, the application of the polymer gel in seedlings tubes and sachets has no effect on plant growth. The irrigation of seedlings in tubes should be made preferably twice a day. The daily irrigations in seedling bags can harm their development.